Bullyng y autoestima en estudiantes de 5to y 6to Grado de Primaria de la Institución Educativa Ruy Guzman Hidalgo Belén 2023 - Parana Pinedo, Daniela (2024)
The objective was to determine the relationship that exists between bullying and self-esteem in 5th and 6th grade primary school students at the Ruy Guzman Hidalgo Educational Institution, Belén 2023. The study had a quantitative approach, with a non-experimental, descriptive, correlational and transversal design; whose population was made up of 163 students. The survey technique was used, the instruments used were the questionnaire on bullying (validity 95%, reliability of 0.92%) and self-esteem (validity 95% reliability of 0.80%). The results were that: 59.5% of students presented a low level of bullying, 39.3% of students presented a medium level of bullying and 1.2% of students presented a high level of bullying. Regarding the level of self esteem, the students presented: 60.1% of students presented high self esteem, medium self-esteem 6.8% and 33.1% of students presented a low level of self-esteem. Concluding, there is significance between bullying and self-esteem (p = 0.001< α 0.05) in 5th and 6th grade primary school students at the Ruy Guzman Hidalgo Educational Institution in the district of Belén, 2023.